3x-105:21=19
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)3x - 105 : 21 = 19
3x - 5 = 19
3x = 19 + 5
3x = 24
x = 24 : 8
x = 3
b, x - 7 = 14 - 3 . 23
x - 7 = 14 - 3 . 8
x - 7 = 14 - 24
x - 7 = -10
x = (-10) + 7
x = -3
HT và $$$
Bài 2:
a) 3x - 105 : 21= 19 b) x - 7= 14 - 3 . 2^3
3x - 5 = 19 x - 7= 14 - 3.8
3x = 19+ 5 x - 7= 14 - 24
3x = 24 x - 7= -10
x = 24 : 3 x = -10+7
x = 8 x = -3
\(P=\dfrac{32}{64}\cdot\dfrac{-57}{19}+\dfrac{35}{21}\cdot\dfrac{22}{44}=\dfrac{1}{2}\left(-3+\dfrac{5}{3}\right)=\dfrac{1}{2}\cdot\dfrac{-4}{3}=\dfrac{-2}{3}\)
\(Q=\dfrac{75}{125}\cdot\dfrac{82}{164}+\dfrac{49}{98}\cdot\dfrac{-35}{105}=\dfrac{1}{2}\left(\dfrac{3}{5}-\dfrac{1}{3}\right)=\dfrac{1}{2}\cdot\dfrac{4}{15}=\dfrac{2}{15}\)
Câu 3:
a) \(\dfrac{12}{36}=\dfrac{12:12}{36:12}=\dfrac{1}{3}\)
\(\dfrac{-16}{20}=\dfrac{-16:4}{20:4}=\dfrac{-4}{5}\)
b) \(\dfrac{21}{105}=\dfrac{21:21}{105:21}=\dfrac{1}{5}\)
\(\dfrac{35}{150}=\dfrac{35:5}{150:5}=\dfrac{7}{30}\)
Câu 4:
a) \(\dfrac{3}{10}+\dfrac{5}{10}=\dfrac{3+5}{10}=\dfrac{8}{10}=\dfrac{4}{5}\)
b) Ta có: \(\left(-27\right)\cdot36+64\cdot\left(-27\right)+23\cdot\left(-100\right)\)
\(=\left(-27\right)\cdot\left(64+36\right)+23\cdot\left(-100\right)\)
\(=-27\cdot100-23\cdot100\)
\(=100\left(-27-23\right)\)
\(=-50\cdot100=-5000\)
c) \(\dfrac{5}{8}+\dfrac{3}{12}=\dfrac{15}{24}+\dfrac{6}{24}=\dfrac{21}{24}=\dfrac{7}{8}\)
d) Ta có: \(\dfrac{-2}{17}+\dfrac{3}{19}+\dfrac{-15}{17}+\dfrac{16}{19}+\dfrac{5}{6}\)
\(=\left(-\dfrac{2}{17}+\dfrac{-15}{17}\right)+\left(\dfrac{3}{19}+\dfrac{16}{19}\right)+\dfrac{5}{6}\)
\(=-1+1+\dfrac{5}{6}\)
\(=\dfrac{5}{6}\)
1) (x-17)*17=0
x-17=0
x=17
2) 32(x-11)=32
x-11=1
x=12
3) (x-25)-75=0
x-25=75
x=3
4) 575-(6*x+70)=445
6*x+70=130
6*x=60
x=10
5) 315+(125-x)=435
125-x=120
x=5
6) x-105:21=15
x-5=15
x=20
7) (x-105):21=15
x-105=315
x=420
8) (x-38):19=12
x-38=228
x=266
9) (x-15)*(x-19)=0
=>x-15=0 hoặc x-19=0
x=15 hoặc x=19
10) 96-3(x+1)=42
3(x+1)=54
x+1=18
x=17
a) ( x - 17 ) . 17 = 0
=> x - 17 = 0 : 17
=> x - 17 = 0
=> x = 0 + 17
=> x = 17
b) 32 . ( x - 11 ) = 32
=> x - 11 = 32 : 32
=> x - 11 = 1
=> x = 1 + 11
=> x = 12
c) ( x - 25 ) - 75 = 0
=> x - 25 = 0 + 75
=> x - 25 = 75
=> x = 75 + 25
=> x = 100
d) 575 - ( 6 . x + 70 ) = 445
=> 6 . x + 70 = 575 - 445
=> 6 . x + 70 = 130
=> 6 . x = 130 - 70
=> 6 . x = 60
=> x = 60 : 6
=> x = 10
e) 315 + ( 125 - x ) = 435
=> 125 - x = 435 - 315
=> 125 - x = 120
=> x = 125 - 120
=> x = 5
f) x - 105 : 21 = 15
=> x - 5 = 15
=> x = 15 + 5
=> x = 20
g) ( x - 105 ) : 21 = 15
=> x -105 = 15 . 21
=> x - 105 = 315
=> x = 315 + 105
=> x = 420
h) ( x - 38 ) : 19 = 12
=> x - 38 = 12 . 19
=> x - 38 = 228
=> x = 228 + 38
=> x = 266
i) ( x - 15 ) . ( x - 19 ) = 0
=> x - 15 = 0 => x = 0 + 15 => x = 15
x - 19 = 0 => x = 0 + 19 = x = 19
=> x = 15 ; 19
j) 96 - 3( x + 1 ) = 42
=> 3( x + 1 ) = 96 - 42
=> 3( x + 1 ) = 54
=> x + 1 = 54 : 3
=> x + 1 = 18
=> x = 18 - 1
=> x = 17
\(\dfrac{19}{21}< \dfrac{x}{y}< \dfrac{7}{6}\Rightarrow\dfrac{38}{42}< \dfrac{x}{y}< \dfrac{49}{42}\Rightarrow\dfrac{x}{y}\in\left\{\dfrac{13}{14};\dfrac{20}{21};\dfrac{41}{42}\right\}\)
Xét \(\dfrac{x}{y}=\dfrac{13}{14}\Rightarrow\dfrac{x}{13}=\dfrac{y}{14}=\dfrac{3x-2y}{39-28}=\dfrac{5}{11}\Rightarrow\left\{{}\begin{matrix}x=\dfrac{65}{11}\\y=\dfrac{70}{11}\end{matrix}\right.\)
Xét \(\dfrac{x}{y}=\dfrac{20}{21}\Rightarrow\dfrac{x}{20}=\dfrac{y}{21}=\dfrac{3x-2y}{60-42}=\dfrac{5}{18}\Rightarrow\left\{{}\begin{matrix}x=\dfrac{50}{9}\\y=\dfrac{35}{6}\end{matrix}\right.\)
Xét \(\dfrac{x}{y}=\dfrac{41}{42}\Rightarrow\dfrac{x}{41}=\dfrac{y}{42}=\dfrac{3x-2y}{123-84}=\dfrac{5}{39}\Rightarrow\left\{{}\begin{matrix}x=\dfrac{205}{39}\\y=\dfrac{70}{13}\end{matrix}\right.\)
(-105) . 19 + (-76) . 105 - 5 . 105
= 105 . (-19) + (-76) . 105 - 5 . 105
= 105 . [(-19) + (-76) - 5]
= 105 . (-100)
= -10500
= ( - 105 )( 19 - 76 - 5 )
= ( - 105 )( - 62 )
= 6510
a.\(3x-20=2^3.5\)
\(3x-20=40\)
\(3x=60\)
\(x=20\)
b.\(3x-9=3^2\)
\(3x=18\)
\(x=6\)
c.\(26-2x=2^2\)
\(2x=22\)
\(x=11\)
x=434 nha
TL:
x=8 nha bạn
-học tốt-